A Case Report of Membranoproliferative Glomerulonephritis: Infection‐Related or Immune‐Related? - Ayman Azhary; Mohammed Taha; Nooh Mohamed Hajhamed; Salahaldeen Ismail Mohammed; Nouh Saad Mohamed; Waleed Azhary Sir Alkhatim (Clinical Case Reports)
ABSTRACT Membranoproliferative glomerulonephritis (MPGN) has previously been used as an umbrella term to describe a spectrum of hypocomplementemic glomerular diseases, which are rare causes of end stage kidney disease (ESKD). We present a 22‐year‐old man with a well‐established medical history who had been complaining of 4 days of frothy dark urine, bilateral lower limb swelling, and puffiness on his face. For a month before his presentation, he had many bilateral skin lesions on his lower limbs that were leaking pus. Aside from the scars from the prior skin lesions, he had no other significant medical history, and his examination revealed no abnormalities. His tests revealed nephrotic range proteinuria with a normal renal profile, low serum albumin with low C3 and normal C4, and negative antinuclear antibodies (ANAs) by ELISA. After preliminary studies, we concluded that the condition was infection‐related glomerulonephritis. Nevertheless, following renal biopsy, which revealed an MPGN pattern, and immunohistochemistry, which revealed a full house picture, we conducted a second ANA test using the more sensitive/broader spectrum IFA hep2 cell test, which showed a coarse speckled nuclear pattern with a significant titer (1/1000), as well as a negative line blot assay test using 15 distinct antigens. Following the modification of our diagnosis to lupus nephritis, the patient responded fairly well once we started him on an immunosuppressive drug. The patient was released from the hospital in a stable condition.